Doping in tennis, where we are and where we should be going? - Zandonai, T.; Holgado, D. (Performance Enhancement & Health, 2020)
The lack of studies concerning doping in tennis is evident. Doping rumours give rise to easy simplistic speculation around tennis players. Projects to fight against doping in tennis are needed.